High Intensity Focused Ultrasound (HIFU): a useful alternativechoice in prostate cancer treatment. Preliminary results - Maestroni, U.; Ziveri, M.; Azzolini, N.; Dinale, et al., F. (Acta Biomedica Atenei Parmensis, 2008)
Introduction and aims: High-Intensity Focused Ultrasound (HIFU) represents an alternative choice in mini-invasive treatment of prostate cancer. The technology of the device used to perform the treatment allows to exactly destroy a pre-selected area and to save all the tissues around it. We report our experience on the effectiveness and complications of this tecnique. Materials and methods: From May 2006 to April 2007, 25 patients with prostate cancer were treated through Ablatherm® (EDAP France) in spinal anesthesia. In the first six patients HIFU and TUR-P (Trans-Urethral Resection of Prostate) were performed in the same session and a suprapubic catheter was placed. In the other 14 patients HIFU was afterwards performed. In these patients a trans-urethral catheter was placed. All patients were divided into three groups: low risk (17 patients), intermediate risk (6 patients) and high risk (2 patients). The follow-up consisted in PSA evaluation after 1,3,6,9,12 months and in transrectal biopsy after six months. Complications related to the treatment, and symptomatological and sexual life tests were evaluated before and after the treatment. Results: HIFU overall success rate was 84% (biochemical relapses in only 4 patients out of 25). Success rate was represented as follows: 94,2 % in the low risk group, 83,4% in the intermediate risk group and 0% in the high risk group. No complications occurred during the treatment nor in the immediately post-operative time. Conclusions: We demonstrated that HIFU represents a useful alternative choice in mini-invasive therapy of prostate cancer. Particularly, results are remarkable in localized (low-intermediate risk) and low morbility prostate cancer. The role of this procedure in high risk patients needs to be further evaluated. Transrectal HIFU represents a mini-invasive therapeutic option that makes the treatment of prostate cancer possible in 84 % of cases. Our results agree with the literature data and demonstrate that the success of the procedure depends on the correct indication of treatment and is strictly related to progression risk parameters.